VARIASI CANGKANG GASTROPODA EKOSISTEM MAI\GROVE CILACAP SEBAGAI ALTERNATIF SUMBER PEMBELAJARAN MOLUSKA; GASTROPODA - KARYANTO, PUGUH; MARIDI, MARIDI; INDROWATI, METI (BIOEDUKASI, 2004)
The aim of this research was to identify some characters of mangrove gastropod's shell, which varied among species and modified from its basic structure. Some characters are often lost or added make some difficulties for the student to identify the characters. Those characters are also confusing and lead to miss identification respectively. From that case, studying the vaiation of the shell characters among species and its modification from the original structure of gastropod's shell is needed. A model and description of the shell and its characters is useful guide for identification and also as an alternative teaching material for studying the gastropod. Mangrove gastropod's specimens from previous research (Karyanto et all, 2003) are the mateials studied on; represent the numerous variation and modification of gastropod's shell. The basic structures are identified according to Robert et al (1952), Pechenik (1991) and Beesley et al (1998). Variation and modification whether reduction or addition from its original were then mentioned and schemed. The shells of the 9 families of gastropod show some specific features, which respective to the shell structure of family, thus the identification to the family can be carried out by using the shell characters of family. Some characters that led to the genera and species are more various and sophisticate. Axial ridges, transversal ridges, eroded apex, elongated siphonal canal, spine, thickened aperture, The presence of the-apterture teeth, thickening operculwm witk calcareous material and coloration are some variant that obtained. Those characters reflect modification and play some important notes while studying the shell.Key words: Mangrove gastropods, shell variation, alternative learning resources